Analysis of biodeterioration wood estate: use different techniques to obtain images - Alfieri,Paula Vanesa (2018)
ABSTRACT This study was based on the current status of locomotive turntable of Provincial Railway Station in La Plata. It was inaugurated in 1910 and it was declared as architectural heritage in 2006. The locomotive turntable is 200 meters from this station and it is a structure that consists in wooden slats of Schinopsis sp. into metal framework. Currently, this structure shows an advanced status of degradation caused by environmental and biological factors. The objective of this work was to determine the wood fungal degradation by non-destructive methods: area occupied by fungus (mycelium and basidiomata) were observed by X-ray radiography (XR) and Computer tomography (TC) and quantified by image analysis with ImageJ software. To establish the microstructural degradation (cell wall), ultrathin cut were analyzed by scanning electron microscopy (SEM). The radiographic images were analyzed by ImageJ and allowed to determinate that the affected area by wood decay fungus inside wood was higher than outside (superficial view). This confirms that external degradation did not correlate with the internal status. TC images showed internal wood structure loss, which were correlated with the presence of fungal hyphae along the entire slat. Finally, wood microstructure was analyzed by SEM, in these images could be observed the advanced deterioration status of the wood structure, where there are high fungal colonization (hyphae) and wood microstructure loss (the cell wall was degraded). This deterioration analysis allows an indirect measurement of the structural condition of the material without destroying it. It was concluded that degradation analysis by images is a non-destructive alternative, and validated methodology to determine material status. This is essential in heritage conservation because it allows defining correctly the degradation status that is useful to planning a conservation strategy, avoiding the asset loss.